Security Challenges and Electoral Malpractice in 2015, 2019, and 2023 General Elections in Cross River Southern Senatorial District, Nigeria - Peter Tom Akwauyama (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The study was designed to investigate security challenges and electoral malpractice in Nigeria's general election in the Southern Senatorial District of Cross River State (2015 to 2023). To achieve the aims of the study, two research questions were raised, and two null hypotheses were formulated to guide the study. The literature review was reviewed based on the related variables and hypotheses formulated. Ex-post facto research design was adopted for the study. The population of the study consists of two thousand five hundred and ninety-six (2596). A total sample of two hundred and sixty (260) respondents was selected for the study. The selection was done through a stratified sampling technique. The main instrument used was a research questionnaire on security challenges and electoral malpractice in Nigeria's general election in the Southern Senatorial district of Cross River State (2015 to 2023) validated by two experts in the test and measurement department, and the department of public administration, Faculty of Management Sciences, University of Calabar. The questionnaire was administered personally by the researcher. To test the hypotheses, Simple linear regression analysis was used. All the hypotheses were subjected to testing at.05 level of significance with critical values. The result of the findings revealed that vote buying as a result of security challenges, ballot box snatching and voter intimidation significantly relate to electoral malpractice in the Cross-River State 2015 to 2023 general election. In conclusion, the study revealed negative relationships between the variables under study and electoral malpractices in southern senatorial district of Cross River State from 2015 to 2023.It was recommended among others that adequate and proper training and retraining of individuals before, during and after election should be ensured to prepare them with the right and necessary skills needed to control violent election and political atmosphere for a credible process in the state to avoid vote buying in the bulling unit.